The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/1687814020959568
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of nonlinear stratified convective flow of Powell-Eyring fluid: Application of modern diffusion

Abstract: The stratification phenomena have great importance in fishery management, insufficiency of dissolved oxygen in the lower parts of lakes, rivers and ponds, and phytoplankton populations. Thus the present article examines vital role of stratification phenomena in Powell-Eyring fluid flow due to inclined sheet which is stretched in a linear way. Collaboration of Cattaneo-Christov heat and mass flux model instead of Fourier Law of heat conduction is also accounted. Interpretation of heat transport is carried out w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Mishra et al [28] conducted a numerical study to probe a steady flow due to a vertical surface subject to double stratified micropolar fluid. An identical study of nanofluid flow and heat transport with thermal stratification has been presented by Abbasi et al [29], Hayat et al [30], Eswaramoorthi et al [31], Jabeen et al [32].…”
Section: Introductionmentioning
confidence: 78%
“…Mishra et al [28] conducted a numerical study to probe a steady flow due to a vertical surface subject to double stratified micropolar fluid. An identical study of nanofluid flow and heat transport with thermal stratification has been presented by Abbasi et al [29], Hayat et al [30], Eswaramoorthi et al [31], Jabeen et al [32].…”
Section: Introductionmentioning
confidence: 78%
“…According to their results, the fluid velocity is high for the Eyring-Powell fluid but Prandtl number and thermal radiation lessen the fluid temperature. Moreover, analysis of nonlinear stratified convection of Eyring-Powell fluid past a sheet, which is inclined and stretching with Cattaneo-Christov heat-mass flux model is presented by Jabeen et al [7]. Their analysis revealed that the thermal stratification parameter and Cattaneo-Chiristov time relaxation dampen the distribution of fluid temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Ali et al [30] depicted phenomenon of dual stratification in Maxwell's nanoliquid flow deformed by stretchable inclined surface considering heat source/sink. Jabeen et al [31] discussed the nonlinear dual stratification analysis in Eyring-Powell material flow under modern diffsion and mixed convection. Malik et al [32] described the Falkner-Skan type movement of nonlinear stratified Jeffrey liquid under the impact of point of stagnation and mixed convection.…”
Section: Introductionmentioning
confidence: 99%